Analysis on Performing Theatrical Performance Matinya Seorang Pahlawan (1992) For Non - Malay Speakers in London - Abdul Walid, Ali; Muhammad Qawiem, Hamizan (Human Resource Management Academic Research Society, 2020)
Matinya Seorang Pahlawan (1992) was one of Malay language theatrical performances that has been performed overseas for non-Malay speakers in SOAS, London. Therefore, surtitles has been introduced in theatre world to overcome the language barrier issue. However, the production has not using surtitles on stage due to some reasons and budged constraint was one of them. This may be difficult for the viewers since foreign performances are alien for the audience members who do not speak the language and do not understand the culture. The research analyses factors and effects on avoiding surtitles on the production. A number of people that involved in the production – theatre makers and viewers were interviewed and documentations and writings about the production are also reviewed in order to get a deeper result on the research. This qualitative research used triangular method to identify and conclude either the production has achieved its main goal to promote Malay language and culture to the world or otherwise.